EFFECTIVENESS TEST OF LARVACIDE FROM COCOR BEBEK LEAF EXTRACT (Kalanchoe pinnata L.) ON Aedes albopictus MOSQUITO LARVAE - Sindi Ahmayanti; Nur Mahdi; Andi Zsazsa RM (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease transmitted by female mosquitoes of the species Aedes aegypti, but sometimes also by Aedes albopictus, which has spread worldwide recently. The goal of this study was to find out how well Kalanchoe pinnata L. (life plant) leaf extract killed Aedes albopictus mosquito larvae. This study used 600 Aedes albopictus larvae in an experimental laboratory setting with a control group that only took the post-test. There were 6 treatment groups: Manila tamarind leaf extract concentrations of 0.2 mg/ml, 0.4 mg/ml, 0.6 mg/ml, and 0.8 mg/ml; a positive control group with temephos; and a negative control group with distilled water. Observations were conducted 24 hours after treatment, with larval mortality counted every hour. The probit analysis indicated that the LC90 for Kalanchoe pinnata L. leaf extract was 12.779 mg/ml, and the LT50 at 0.8 mg/ml, which was the concentration that killed the most quickly, was 48,058 hours. The results show that an extract from Kalanchoe pinnata L. leaves can kill Aedes albopictus mosquito larvae.